Flood hazard zones using 2d hydrodynamic modeling and remote sensing approaches - M.B.T. Alivio; G.R. Puno; B.A.M. Talisay (Global Journal of Environmental Science and Management)
Increasing frequency and severity of flooding demands identification of flood hazard zones in Kalilangan, Bukidnon in response to the echoing need of better disaster preparedness via enhancing the understanding and awareness of the public on flood characteristics by integrating the use of two-dimensional hydrodynamic modeling and remote sensing. Flood simulation was carried out in a two-dimensional hydrodynamic model using hydrologic engineering center-river analysis system to derive the flood inundation area and flood depth of Kalilangan, Bukidnon. Thus, it was preceded by pre-processing of the model using software packages of hydrologic engineering center-hydrologic modeling system and ArcGIS along with interferometric synthetic aperture radar–digital elevation model, Manning’s roughness coefficient and precipitation data. Five different rain return flooding scenarios were simulated using rainfall intensity duration frequency data. Three zones of flood hazard were then set as low, medium and high. The result shows that most areas of Kalilangan are within the zones of medium to high hazard with residential buildings as the most flooded type of built-up structures. Flood hazard zone areas could be mapped at an accuracy of 79.51%. Thus, harnessing this potential approach offers cost-effective way of flood preparedness viewing hazard-prone areas with special attention and utmost importance.